2012
DOI: 10.1007/8904_2012_200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Phonological Awareness Skills in Children with Classic Galactosemia: A Descriptive Study of Four Cases

Abstract: Educational achievement, which for individuals with the metabolic disorder classic galactosemia (GAL) is significantly lower than in the wider population, correlates with self-reported quality of life. Phonological awareness skills underpin the development of literacy, and although literacy is a key contributor to successful academic outcomes, no study to date has investigated phonological awareness skills in children with GAL. This study investigated phonological awareness (PA) in four school-aged children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…These abilities are referred to as cognitive functioning and encompass domains such as information processing speed, attention, memory, visuospatial functioning and executive functioning. Previous studies reporting on cognitive functioning in CG patients demonstrated below average to low functioning on several cognitive domains [5][6][7][8][9]. However, the outcomes on the cognitive domains differed between studies and results must be interpreted with care because studies mostly addressed only one cognitive domain, used one single test per cognitive domain and/or included small cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…These abilities are referred to as cognitive functioning and encompass domains such as information processing speed, attention, memory, visuospatial functioning and executive functioning. Previous studies reporting on cognitive functioning in CG patients demonstrated below average to low functioning on several cognitive domains [5][6][7][8][9]. However, the outcomes on the cognitive domains differed between studies and results must be interpreted with care because studies mostly addressed only one cognitive domain, used one single test per cognitive domain and/or included small cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with galactosemia have impairments in language planning (Potter et al, 2013). Vocabulary, grammar and word retrieval problems have been described (Schweitzer et al, 1993;Waggoner et al, 1990;Waisbren et al, 1983), as well as cases with clinically significant delays on pre-linguistic skills (at age 13 month) (Lewis et al, 2013), and failures to meet age-appropriate phonological awareness (aged 7-9) (Lewis et al, 2012). The majority of patients with galactosemia and history of speech sound disorders also have language disorders, which cannot be explained by lower cognitive abilities (Potter et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…An over restricted galactose diet impairs myelin synthesis secondary to a deficit of galactolipids (galactocerebrosides) and glycoproteins, that is hypoglycosilated because of increased production of nongalactosylated or mono-galactosylated proteins [4,9,[11][12][13]. It has been observed In Vivo that the increased levels of galactose 1-phosphate inhibit glucose pyrophosphorylase reducing UDPglucose/galactose and responsible for impaired glycosylation of proteins and lipids, such problems are different between individual, because the activation of secondary pathways to metabolize galactose can be epigenetic regulated and depend on the individual's genetic characteristics [9,12].…”
Section: Glycosylation Impairmentmentioning
confidence: 99%
“…The treatment goal to maintain galactose 1-phosphate levels below 5 mg/dl with food containing with galactose content of less than 25 mg/100 gr is the backbone of the over restricted diet but is responsible for the impaired glycosylation of proteins leading to decreased white matter synthesis and the posterior neurological symptoms; and increased levels of galactose 1-phosphate are prone to induce oxidative stress and caused neurotoxicity [2][3][4][11][12][13][17][18][19].…”
Section: Conclusion: Over Restricted Diet or Notmentioning
confidence: 99%
See 1 more Smart Citation